The Influence of Family, School, and Community Environments on Students’ Academic Achievement in Science Learning - Devi Lestari; Aprilia Tina Lidyasari (Jurnal Penelitian Pendidikan IPA, 2024)
This research was conducted because the academic achievement of students in class V science subjects at SDN Umbulharjo District is still low. The aim of this research is to discuss the reasons why academic achievement can change, one of which can come from the family environment, school environment and home environment and how the learning environment influences the student's academic achievement. The method used in this research is ex post fact. The data collection method is carried out by documenting students' reported grades and using questionnaire items. The population is 214 students. The results of analysis using multiple linear regression show that there is a positive influence of the family, school and community environment on student academic achievement. Furthermore, the effective contribution (SE) test obtained a value of 80.5%, which means the influence of the learning environment on student academic achievement and another 19.5% was influenced by other factors not included in this research.